Comparing the Natural Mating with Artificial Insemination (A.I) at Mazandran Native Hen - Koohpar, H. Khazaei; Sayyahzadeh, H.; Pirsaraei, Z. Ansari (International Journal of Poultry Science, 2010)
At the present study, a comparison was done between the natural mating and the A.I. in Mazandran native hen. 100 females and 10 males were randomly selected from the native hen flock, one male was determined per each ten females. First the natural mating was done between the flock. Each female’s egg was determined using trap nest and each individual female and males chicken’s number was counted at the end of the test. The male were removed from the boxes for insemination and then the males were ready for collecting the semen. The abdominal rubbing of the males were done by using the Burous method and the resulting semen were immediately diluted using the low fat milk and 0.1cc of semen was inseminated to each female and the insemination was reported after each six days. The egg collecting stage and the stages following the same as the natural mating. The results of the statistical analysis showed that there is no significant difference between the fertility and hatchability traits of these two models (p>0.36). Yet the A.I. helped to mate the males and females having no mating will and thus the hatchability percentage increased. On the other hand, the male’s keeping cost decreased.